Consistent Microbial Assembly in the Rhizosphere of Crop Wild Progenitors - Miguel de Celis; María José Fernández‐Alonso; María Leo; Ignacio Belda; Carlos García; Brajesh K. Singh; Yue Yin; Juntao Wang; Juan Gaitán; Luis Abdala‐Roberts; Fernando D. Alfaro; Diego F. Angulo; et al. (Global Ecology and Biogeography, 2026)
Aim Microbiome rewilding seeks to harness plant‐microbe interactions for sustainable agriculture, assuming that ancestral microbial partners have been lost during domestication and geographical spread. Designing microbiome rewilding strategies requires a quantitative and predictive understanding of the fundamental ecological processes—selection, dispersal, and drift—driving microbial assembly and persistence in the rhizosphere of crop wild progenitors (CWPs). Location Global. Time Period Present. Major Taxa Studied Rhizosphere bacteria and fungi. Methods Here, we leveraged a global survey of the CWPs of 10 major crops across their native habitats to assess the roles of selection, dispersal, and drift in shaping rhizosphere microbial communities. We combined compositional and phylogenetic turnover metrics with local network analyses to evaluate community assembly and structure in response to environmental gradients. Results We found host‐driven selection, reflected by low phylogenetic turnover at the whole‐tree level, but also selection driven by differences among individual plants, as indicated by high turnover among closely related taxa. The high level of compositional turnover found suggests dispersal limitations, which in the context of CWPs, may indicate host‐mediated filtering of external microbial taxa. The network structure was constant across CWPs; however, bacterial and fungal structures diverged, pointing to distinct community organisations. Bacterial communities presented higher modularity and lower clustering than fungal communities. Climate, especially seasonal temperature and precipitation, was the main driver of both bacterial and fungal structures. However, host identity best predicted bacterial structure, while NDVI, a proxy for vegetation status, better explained fungal patterns. Main Conclusions Bacterial and fungal communities are shaped by consistent assembly processes across CWPs, but their structures diverge. With the identification of the assembly processes driving microbiome composition in the rhizosphere of CWPs, this work paves the road to incorporate microbiome rewilding in the toolbox of sustainable agriculture.

Wine Fermentation as a Model System for Microbial Ecology and Evolution - Ignacio Belda; Sergio Izquierdo‐Gea; Belen Benitez‐Dominguez; Javier Ruiz; Jean C. C. Vila (Environmental Microbiology, 2025)
In vitro microbial communities have proven to be invaluable model systems for studying ecological and evolutionary processes experimentally. However, it remains unclear whether quantitative insights obtained from these laboratory systems can be applied to complex communities assembling and evolving in their natural ecological context. To bridge the gap between the lab and the ‘real‐world’, there is a need for laboratory model systems that better approximate natural and semi‐natural ecosystems. Wine fermentation presents an ideal system for this purpose, balancing experimental tractability with rich ecological and evolutionary dynamics. In this perspective piece we outline the key features that make wine fermentation a fruitful model system for ecologists and evolutionary biologists. We highlight the diversity of environmentally mediated interactions that shape community dynamics during fermentation, the complex evolutionary history of wine microbial populations, and the opportunity to study the impact of complex ecologies on evolutionary dynamics. By integrating knowledge from both wine research and microbial ecology and evolution we aim to enhance understanding and foster collaboration between these fields.

The abundant fraction of soil microbiomes regulates the rhizosphere function in crop wild progenitors - Miguel de Celis; María José Fernández‐Alonso; Ignacio Belda; Carlos García; Raúl Ochoa‐Hueso; Javier Palomino; Brajesh K. Singh; Yue Yin; Jun‐Tao Wang; Luis Abdala‐Roberts; Fernando D. Alfaro; Diego Angulo‐Pérez; et al. (Ecology Letters, 2024)
The rhizosphere influence on the soil microbiome and function of crop wild progenitors (CWPs) remains virtually unknown, despite its relevance to develop microbiome‐oriented tools in sustainable agriculture. Here, we quantified the rhizosphere influence—a comparison between rhizosphere and bulk soil samples—on bacterial, fungal, protists and invertebrate communities and on soil multifunctionality across nine CWPs at their sites of origin. Overall, rhizosphere influence was higher for abundant taxa across the four microbial groups and had a positive influence on rhizosphere soil organic C and nutrient contents compared to bulk soils. The rhizosphere influence on abundant soil microbiomes was more important for soil multifunctionality than rare taxa and environmental conditions. Our results are a starting point towards the use of CWPs for rhizosphere engineering in modern crops.

Impact of rare yeasts in Saccharomyces cerevisiae wine fermentation performance: Population prevalence and growth phenotype of Cyberlindnera fabianii, Kazachstania unispora, and Naganishia globosa - Javier Vicente; Javier Ruiz; Sandra Tomasi; Miguel de Celis; Candela Ruiz-de-Villa; Jordi Gombau; Nicolás Rozès; Fernando Zamora; Antonio Santos; Domingo Marquina; Ignacio Belda (Food Microbiology, 2023)

Global distribution of IRC7 alleles in Saccharomyces cerevisiae populations: a genomic and phenotypic survey within the wine clade - Javier Ruiz; Miguel de Celis; María Martín‐Santamaría; Iván Benito‐Vázquez; Ana Pontes; Val F. Lanza; José Paulo Sampaio; Antonio Santos; Ignacio Belda (Environmental Microbiology, 2021)
Summary The adaptation to the different biotic and abiotic factors of wine fermentation has led to the accumulation of numerous genomic hallmarks in Saccharomyces cerevisiae wine strains. IRC7 , a gene encoding a cysteine‐S‐β‐lyase enzyme related volatile thiols production in wines, has two alleles: a full‐length allele ( IRC7 F ) and a mutated one ( IRC7 S ), harbouring a 38 bp‐deletion. Interestingly, IRC7 S ‐encoding a less active enzyme – appears widespread amongst wine populations. Studying the global distribution of the IRC7 S allele in different yeast lineages, we confirmed its high prevalence in the Wine clade and demonstrated a minority presence in other domesticated clades (Wine‐PDM, Beer and Bread) while it is completely missing in wild clades. Here, we show that IRC7 S ‐homozygous (HS) strains exhibited both fitness and competitive advantages compared with IRC7 F ‐homozygous (HF) strains. There are some pieces of evidence of the direct contribution of the IRC7 S allele to the outstanding behaviour of HS strains (i.e., improved response to oxidative stress conditions and higher tolerance to high copper levels); however, we also identified a set of sequence variants with significant co‐occurrence patterns with the IRC7 S allele, which can be co‐contributing to the fitness and competitive advantages of HS strains in wine fermentations.

Membrane bioreactor wastewater treatment plants reveal diverse yeast and protist communities of potential significance in biofouling - Raquel Liébana; Lucía Arregui; Ignacio Belda; Luis Gamella; Antonio Santos; Domingo Marquina; Susana Serrano (Biofouling, 2015)

Endangered subspecies of the Reed Bunting (Emberiza schoeniclus witherbyi and E. s. lusitanica) in Iberian Peninsula have different genetic structures - Laura Kvist; Suvi Ponnikas; Eduardo J. Belda; Ignacio Encabo; Emilio Martínez; Alejandro Onrubia; José M. Hernández; Pablo Vera; Júlio M. Neto; Juan S. Monrós (Journal of Ornithology, 2011)